Analysis of a Predator-Prey Model incorporating Prey Cannibalism and Intraspecific Competition on Predator - Biduli, Meiske; Rahmi, Emli; Nasib, Salmun K. (Indonesian Journal of Computational and Applied Mathematics, 2025)
In this research, we formulated a predator-prey model by considering cannibalism in the prey and intraspecific competition on predator population. We found three types of equilibrium points existed under certain condition, except the extinction of all population equilibrium point. Further, we analyzed the local stability of each equilibrium point via linearization method. We found that the extinction of all population equilibrium point is always unstable and the other points locally asymptotically stable under some conditions. Finally, the numerical simulation carried out to verify the analytical results and to perform the impact of prey cannibalism rate.